Cations Coordination‐Regulated Reversibility Enhancement for Aqueous Zn‐Ion Battery. (14th July 2021) - Qian, Long; Yao, Wentao; Yao, Rui; Sui, Yiming; Zhu, Haojie; Wang, Fangcheng; Zhao, Jianwei; Zhi, Chunyi; Yang, Cheng
Abstract: Aqueous Zn‐ion batteries are emerging as a promising candidate for large‐scale energy storage, while the short lifetime and poor reversibility of Zn anodes limit their further development. When attempting to enhance reversibility, most reported methods involve toxic and pollutive substances and decreased water content, which inevitably sacrificed safety level, rate performance, and environmentally benign characteristics. Herein, a series of low‐cost and "green" molecules are introduced into the aqueous (ZnCl2, ZnSO4 ) electrolytes, featured with cations coordination capability, which can significantly inhibit the hydration step of Zn 2+ and delay the formation of the key by‐products (Zn5 (OH)8 Cl2 ·H2 O, 3Zn(OH)3 ·ZnSO4 ·5H2 O) in aqueous electrolytes via regulating the coordination status of Zn 2+ . In the optimized electrolyte system, a highly reversible Zn metal anode presents excellent electrochemical performance, featured with a long lifespan over 1185 h at 1 mA cm −2 and smooth deposition morphology. Furthermore, Zn–MnO2 batteries based on the electrolyte deliver high capacity retention of 82.9% after 200 cycles. These breakthroughs suggest that this method offers a versatile toolbox toward developing future advanced multivalent metal batteries for large‐scale energy storage. Abstract : The introduction of electron‐donating substituents can improve the electron‐donating capacity of ligands, a critical factor in the cation coordination process. In this way, the formation of Zn(OH2 )6 2+, which is a key species that leads to the formation of by‐products through dehydrogenation, is well inhibited. This method can improve the efficiency of Zn metal plating/stripping in a water‐abundant electrolyte.